2018
DOI: 10.1136/bmjopen-2017-020897
|View full text |Cite
|
Sign up to set email alerts
|

How do ED patients with criminal justice contact compare with other ED users? A retrospective analysis of ED visits in California

Abstract: ObjectiveTo assess the patterns of emergency department (ED) utilisation among those with and without criminal justice contact in California in 2014, comparing variation in ED use, visit frequency, diagnoses and insurance coverage.DesignRetrospective, cross-sectional study.SettingAnalyses included ED visits to all licensed hospitals in California using statewide data on all ED encounters in 2014.ParticipantsStudy participants included 3 757 870 non-elderly adult ED patients who made at least one ED visit in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…About 80-90% of criminal perpetrators need medical treatment under health problems such as mental problems, surgery, chronic disease, and drug abuse record. However, the growing concern about this deal with the occurring gaps and discrimination in administering health services (3)(4)(5). Nurses in a hospital have important roles in delivering health services for the criminals, started when they access the health facility until the referral process.…”
Section: Introductionmentioning
confidence: 99%
“…About 80-90% of criminal perpetrators need medical treatment under health problems such as mental problems, surgery, chronic disease, and drug abuse record. However, the growing concern about this deal with the occurring gaps and discrimination in administering health services (3)(4)(5). Nurses in a hospital have important roles in delivering health services for the criminals, started when they access the health facility until the referral process.…”
Section: Introductionmentioning
confidence: 99%
“…However, developing apprehension deals with the gap in administering health services in that population. Criminals usually are attached to stigma and discrimination from society, including the nurses (Dhaliwal & Hirst, 2016;McConville et al, 2018;Melillo, 2009;Redgewell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 Another California study found that most ED utilization for people who experienced imprisonment was for mental health conditions, and this population had a higher proportion of frequent ED use than the general population. 9 Research on ED use in people who experience imprisonment is limited, however, by a focus on subpopulations, [7][8][9] examination of only the post-release period, 5,8 and having been conducted only in the United States, in which there is a lack of universal health insurance. 5,[7][8][9] Population-based data on ED utilization could offer valuable insights regarding the health status, healthcare needs, and access to care for this structurally vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research on ED use in people who experience imprisonment is limited, however, by a focus on subpopulations, [7][8][9] examination of only the post-release period, 5,8 and having been conducted only in the United States, in which there is a lack of universal health insurance. 5,[7][8][9] Population-based data on ED utilization could offer valuable insights regarding the health status, healthcare needs, and access to care for this structurally vulnerable population. Building on initial research on healthcare utilization for this population across settings, 10 our objective was to describe the ED utilization of men and women in prison and after release, and to compare these data with data for the general population in Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%